Pengaruh Jenis Cairan, Jenis Batang, dan Panjang Batang pada Penentuan Distribusi Ukuran Partikel Bubuk Kaca Menggunakan Buoyancy Weighing-Bar Method (BWM) - Panjaitan, Ari Fernando; Sirait, Anrocki; Tambun, Rondang (Jurnal Teknik Kimia USU, 2024)
Particle size distribution is one of the important physical parameters in industry. A new method has been developed, the buoyancy weighing-bar method to determine the particle size distribution. This study examines the application of the buoyancy weighing-bar method for the determination of the particle size distribution of glass powder. Measurements were made by varying the type of liquid, the type of rod, and the size of the rod length. From this study, it was obtained that the best condition in determining the particle size distribution of glass powder is using aluminum rods with a length of 210 mm in 96% ethanol. The results of determining the particle size distribution of glass powder by using the buoyancy weighing-bar method at the best conditions are comparable to the results of determining the particle size distribution obtained using the settling balance method.